Transient increase of interferon-stimulated genes and no clinical benefit by chloroquine treatment during acute simian immunodeficiency virus infection of macaques. - Vaccari, M; Fenizia, C; Ma, Z; Hryniewicz, A; Boasso, A; Doster, M; Miller, C; Lindegardh, N; Tarning, J; Landay, A; Shearer, G; Franchini, G (Mary Ann Liebert Inc., 2014)
Simian immunodeficiency virus (SIV) infection leads to AIDS in experimentally infected Rhesus macaques similarly to HIV-infected humans. In contrast, SIV infection of natural hosts is characterized by a down-regulation of innate acute responses to the virus within a few weeks of infection and results in limited pathology. Chloroquine (CQ) has been used in the treatment or prevention of malaria and has recently been shown to cause a decrease of immune activation and CD4 cell loss in HIV-infected individuals treated with antiretroviral therapy. Here, we treated Rhesus macaques with CQ during the acute phase of SIVmac251 infection with the intent to decrease viral-induced immune activation and possibly limit disease progression. Contrary to what was expected, CQ treatment resulted in a temporary increased expression of interferon (IFN)-stimulating genes and it worsened the recovery of CD4(+) T cells in the blood. Our findings confirm recent results observed in asymptomatic HIV-infected patients and suggest that CQ does not provide an obvious benefit in the absence of antiretroviral therapy.